Non-English Speaking Background Effects on Hospitality Front Desk Services: A Case Perspective from Western Australia - Suwarto, Titania (Curtin University, 2022)
Understanding cultural diversity in service delivery is crucial because different cultures have different traditions in conceptualising service delivery and quality. By employing interviews with 31 tourists, employees, and employers of serviced apartments in Western Australia (WA), this qualitative study finds that the cultural background of non-English speaking background front-desk staff might influence the essential attributes of front-desk services delivery, particularly attitude/ personality, communication skill, knowledge, experience, and understanding.